A dual-continuous phase eutectic polymer solid electrolyte and soft-pack battery and preparation method

By adopting a bicontinuous phase eutectic polymer solid electrolyte, combining the ion-conducting phase and the inert support phase, the problems of polymer solid electrolyte in both electrochemical stability, ion conductivity and mechanical strength are solved, achieving high performance and simplification Effects of the preparation process.

CN119230933BActive Publication Date: 2025-02-07SHANDONG LIANCHUANG POLYMER CO LTD

Patent Information

Application Number
CN202411730532.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-07
Estimated Expiration
2044-11-29

AI Technical Summary

Technical Problem

In the prior art, polymer solid electrolytes have problems such as poor compatibility with electrode interfaces, inability to have both ion conductivity and mechanical strength, and complex preparation process, which affect the overall performance and stability of the battery.

Method used

The solid electrolyte of bicontinuous phase eutectic polymer is made of a combination of a bicontinuous phase polymer film and a eutectic compound. The ion-conducting phase is combined with an inert support to design a process of "film making first, then swelling" and adapt to "first" Assemble, after-filling liquid” battery assembly process.

Benefits of technology

It has achieved polymer solid electrolytes with good electrochemical stability, high ionic conductivity and high mechanical strength, simplified the battery preparation process, reduced production costs, and met low cost and industrialization requirements.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

A dual-continuous phase eutectic polymer solid electrolyte and soft-pack battery and preparation method, belonging to the technical field of secondary batteries. The solid electrolyte is made by infiltrating and adsorbing a eutectic compound on a dual-continuous phase polymer membrane, the dual-continuous phase polymer membrane is made by dissolving an ion-conducting phase and an inert supporting phase in a polar solvent and casting the membrane, the eutectic compound is composed of lithium salt and organic small molecules; the ion-conducting phase is eutectic compound-friendly, and the inert supporting phase is eutectic compound-scarce. The electrolyte prepared by the present invention has high electrochemical stability of positive and negative electrodes, high ionic conductivity, and high strength characteristics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary batteries, and in particular relates to a dual-continuous phase eutectic polymer solid electrolyte and a soft-pack battery and a preparation method thereof. Background Art

[0002] Currently, commercial liquid electrolytes have safety hazards such as flammability and volatility, and low energy density (230Wh / Kg), which restricts the application and development of batteries. Polymer solid-state batteries have good plasticity and flexibility, and can be in close contact with electrode materials. Polymer solid-state batteries have been widely studied in the past few decades. However, polymer electrolytes still have disadvantages such as poor compatibility with electrode interfaces, inability to achieve both ionic conductivity and mechanical strength, and complex preparation processes.

[0003] Patent CN109935894A discloses a montmorillonite-based lithium battery solid electrolyte and its preparation method. The lithium battery solid electrolyte includes the following components: ionic liquid, lithium salt and montmorillonite, and the lithium battery solid electrolyte is prepared by heating. The lithium battery solid electrolyte of the invention is a new type of electrolyte that has the advantages of both liquid electrolyte and solid electrolyte. However, the processability and compatibility of montmorillonite with electrode materials in the technology are not as good as other types of solid electrolytes, which will affect the overall performance and stability of the battery. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the deficiencies of the prior art and provide a dual-continuous phase eutectic polymer solid electrolyte and a soft-pack battery and a preparation method thereof with good electrochemical stability, high ionic conductivity and high mechanical strength.

[0005] The technical solution adopted by the present invention to solve its technical problems is: a dual-continuous phase eutectic polymer solid electrolyte, which is made by infiltrating and adsorbing a eutectic compound on a dual-continuous phase polymer membrane, wherein the dual-continuous phase polymer membrane is made by dissolving an ion conductive phase and an inert supporting phase in a polar solvent and casting the membrane, and the eutectic compound is composed of a lithium salt and an organic small molecule; wherein the ion conductive phase is a eutectic compound-affinity, and the inert supporting phase is a eutectic compound-dispersion.

[0006] In solid electrolytes, high mechanical strength is achieved by the inert supporting phase, while high ionic conductivity is achieved by the combination of the ion-conducting phase and the eutectic compound.

[0007] During the preparation, the ion-conducting phase and the inert supporting phase are dissolved in a polar solvent and cast into a film to obtain a dual-continuous phase polymer membrane; the lithium salt and the organic small molecule are blended at 60°C to 80°C to form a eutectic compound, and the dual-continuous phase polymer membrane is infiltrated and adsorbed in the eutectic compound to obtain a dual-continuous phase eutectic polymer solid electrolyte. Preferably, the mass ratio of the dual-continuous phase polymer membrane to the eutectic compound in the infiltration and adsorption is 1~8:1. The temperature of the infiltration and adsorption is 70°C~90°C, and the time is 3h~5h. The preparation of the dual-continuous phase eutectic polymer solid electrolyte is to prepare an electrolyte membrane by the "first membrane, then swelling" process of the dual-continuous phase polymer membrane and the eutectic compound. More preferably, the mass ratio of the dual-continuous phase polymer membrane to the eutectic compound is 1~4:1.

[0008] The present invention designs weak Li + Coordination electrolytes, "double continuous phase local high concentration polymer electrolyte" is proposed. The designed electrolyte is constructed by ion-conducting phase, inert supporting phase and eutectic compound, where the ion-conducting phase is eutectic compound-friendly, while the inert supporting phase is eutectic compound-sparse, which makes the electrolyte produce a local high concentration phenomenon and produces a solid electrolyte interface layer derived from rich anions, thereby solving the problem of poor stability with the positive and negative electrodes. At the same time, the ion-conducting phase eutectic compound provides high ionic conductivity, while the inert supporting phase eutectic compound provides high mechanical strength, thus realizing a polymer solid electrolyte with both high ionic conductivity and high mechanical strength.

[0009] Preferably, in the above-mentioned dual-phase eutectic polymer solid electrolyte, the mass ratio of the ion-conducting phase to the inert supporting phase in the dual-phase polymer membrane is 1-10:1.

[0010] There is no special requirement for the polar solvent for dissolving the ion-conducting phase and the inert supporting phase. Any polar solvent that can dissolve both of them can be used, such as dimethyl sulfoxide, N,N-dimethylacetamide, etc.

[0011] When preparing a dual-continuous phase polymer membrane, the solid content in the ion-conducting phase and the inert supporting phase polar solvent is 3wt%~20wt%; the heating temperature is 50℃~150℃; the stirring speed is 500r / min~1000r / min; and the stirring time is 6h~8h.

[0012] Preferably, in the above-mentioned dual-continuous phase polymer membrane, the ion-conducting phase is polyether block polyamide, which is a polymer that can be complexed with lithium salt.

[0013] Preferably, in the above-mentioned dual-continuous phase polymer film, the inert supporting phase is polyarylether or polyamide, a relatively rigid polyarylether or polyamide polymer, and further, the inert supporting phase is one of polybenzimidazole, polyimide, polyamic acid or polyvinyl chloride.

[0014] Preferably, in the above-mentioned dual-continuous phase eutectic polymer solid electrolyte, the eutectic compound is a mixture of lithium salt and organic small molecules in a mass ratio of 1:1-10.

[0015] When preparing the eutectic compound, the lithium salt and the organic small molecule are mixed according to the mass ratio at a temperature of 30° C. to 80° C. More preferably, the mass ratio of the lithium salt to the organic small molecule is 1:1 to 5.

[0016] Preferably, in the above eutectic compound, the lithium salt is a Lewis acidic lithium salt compound, including one or more combinations of lithium bis(trifluoromethylsulfonyl imide), lithium bis(difluorosulfonyl imide), lithium bis(oxalatoborate), lithium perchlorate, lithium tetrafluoroborate and lithium hexafluorophosphate.

[0017] Preferably, in the above-mentioned eutectic compound, the organic small molecule is a Lewis base compound, including one or more combinations of amides, nitriles, carbonates, sulfonic acids and sulfonamide molecules.

[0018] More preferably, the lithium salt is lithium bis(trifluoromethylsulfonyl)imide, and the organic small molecule is succinonitrile or N-methylacetamide;

[0019] A method for preparing a soft-pack battery based on the above-mentioned dual-continuous phase eutectic polymer solid electrolyte, characterized in that it comprises the following steps: S1 preparing a battery cell, S2 welding a tab, S3 injecting a eutectic compound, S4 standing at a constant temperature, S5 negative pressure primary pre-packaging, S6 constant temperature and constant pressure activation, and S7 negative pressure secondary packaging process;

[0020] In step S1, the preparation of the battery cell includes: a positive electrode, a negative electrode, and the above-mentioned dual-continuous phase eutectic polymer solid electrolyte are stacked in sequence; the positive electrode includes: one of lithium iron phosphate, ternary lithium, lithium cobalt oxide, and lithium manganese oxide; the negative electrode includes: one of lithium alloy, graphite, carbon silicon, and lithium metal;

[0021] The frequency of welding the tabs in step S2 is 500 Hz to 1500 Hz, and the time is 0.1 s to 1 s; preferably, the frequency of welding the tabs is 1000 Hz, and the time is 0.02 s;

[0022] In step S3, the eutectic compound is injected according to the dosage;

[0023] The constant temperature standing temperature in step S4 is 20°C to 60°C for 4h to 6h; preferably, the standing temperature is 20°C for 4h;

[0024] The vacuum degree of the negative pressure primary pre-packaging in step S5 is -60 kPa to -100 kPa, and the time is 3 s to 5 s; preferably, the vacuum degree is -82 kPa, and the time is 3 s;

[0025] The constant temperature and constant pressure activation in step S6 is performed at a temperature of 60°C to 80°C, a constant pressure of 0.8MPa to 1MPa, and a time of 4h to 6h; preferably, the temperature is 60°C, the pressure is 0.8MPa, and the time is 4h;

[0026] The vacuum degree in the negative pressure secondary packaging process in step S7 is -60kPa~-100kPa, and the time is 3s~5s; preferably, the vacuum degree is -82kPa, and the time is 3s.

[0027] The electrolyte prepared by the present invention has high electrochemical stability, high ionic conductivity and high mechanical strength with positive and negative electrodes. The solid electrolyte membrane preparation strategy of "preparing membrane first, swelling later" is designed to adapt to the existing battery assembly process of "assembling first, injecting liquid later", so that the preparation of electrolyte does not need water and oxygen isolation, greatly simplifying the solid-state battery preparation process and reducing production costs, meeting the requirements of low cost and industrialization.

[0028] Preferably, in the above-mentioned method for preparing a soft-pack battery, the thickness of the dual-continuous phase polymer film is 10 μm to 30 μm.

[0029] A soft-pack battery uses the above-mentioned dual-continuous phase eutectic polymer solid electrolyte.

[0030] Compared with the prior art, the soft-pack solid-state battery prepared by the present invention has the following beneficial effects: the electrolyte prepared by the present invention has high electrochemical stability of positive and negative electrodes, high ionic conductivity, and high strength characteristics. The present invention designs a solid electrolyte preparation process method of "preparing a membrane first, then swelling", which is adapted to the current battery assembly process of "assembling first, then injecting liquid", so that the preparation of the electrolyte does not require water isolation and oxygen isolation, greatly simplifies the solid-state battery preparation process and reduces production costs, meeting the requirements of low cost and industrialization. DETAILED DESCRIPTION

[0031] The present invention relates to a method for preparing a dual-continuous phase eutectic polymer solid electrolyte and the application of a soft-pack battery in a lithium-ion battery. The technical solution of the present invention will be described in detail in conjunction with an embodiment. The described embodiment is only a part of the present invention and is only used to explain the present invention, not to limit the present invention.

[0032] Example 1

[0033] 1. Preparation of dual-continuous phase polymer membrane: The ion-conducting phase polyether block polyamide and the inert supporting phase fully aromatic polybenzimidazole are blended in a mass ratio of 4:1, dissolved in a polar solvent dimethyl sulfoxide, heated to 120°C in an oil bath, and dissolved by magnetic stirring for 6 hours. After the polymer is completely dissolved, filter it while hot and remove bubbles by ultrasound. On the surface of the glass mold, 15mL of the dual-continuous phase polymer membrane liquid is quickly dripped drop by drop in an area of ​​12×12cm, and the solvent is evaporated at 50°C to form a film. The membrane is taken by soaking in deionized water and dried in a vacuum oven at 100°C for 24 hours to further remove water and solvent. Cut the dried membrane into specified sizes and store it in a dry state.

[0034] 2. Preparation of eutectic compound: lithium salt lithium bis(trifluoromethylsulfonyl)imide and organic small molecule succinonitrile were mixed in a mass ratio of 1:1 at 30°C;

[0035] 3. Preparation of dual-continuous phase eutectic polymer electrolyte: The dual-continuous phase polymer film and the eutectic compound were adsorbed and combined at a mass ratio of 2:1, and allowed to stand for adsorption at 80°C for 4 hours.

[0036] 4. The preparation of soft pack batteries includes the following steps:

[0037] S1: preparing a battery cell: stacking the positive lithium iron phosphate electrode, the obtained dual-continuous phase eutectic polymer electrolyte, and the lithium negative electrode in sequence and fixing them, and encapsulating them with an aluminum-plastic film to obtain a battery cell;

[0038] S2: welding lugs: welding frequency 1000 Hz, time 0.02 s;

[0039] S3: Eutectic compound injection: injection according to the mass ratio of the bicontinuous phase polymer film to the eutectic compound of 2:1;

[0040] S4: Constant temperature standing: The constant temperature standing temperature is 40°C for 4 hours to allow the dual-continuous phase polymer film and the eutectic compound to be fully infiltrated;

[0041] S5: Negative pressure primary pre-packaging: the soaked battery cell is evacuated to negative pressure and packaged, the vacuum degree is -82KPa, and the time is 3s;

[0042] S6: Constant temperature and constant pressure activation: activate the first packaged battery cell in a constant temperature and constant pressure environment, with a constant temperature of 80°C and a constant pressure of 0.8MPa for 6 hours, and test the open circuit voltage and resistance;

[0043] S7: Negative pressure secondary packaging process: the battery is deflated and vacuumed and then packaged again. The vacuum degree is -82KPa and the time is 3s.

[0044] A soft-pack battery with a dual-continuous phase eutectic polymer solid electrolyte has been prepared.

[0045] Example 2

[0046] 1. Preparation of dual-continuous phase polymer membrane: The ion-conducting phase polyether block polyamide and the inert support phase carboxyl-containing polyimide are blended in a mass ratio of 4:1, dissolved in a polar solvent N, N-dimethylacetamide to prepare a membrane solution, heated to 80°C in an oil bath, and magnetically stirred for 6 hours. After the polymer is completely dissolved, 15 mL of the dual-continuous phase polymer membrane liquid is quickly dripped on the surface of the glass mold in an area of ​​12×12 cm, and the solvent is evaporated at 80°C to form a membrane. The membrane is taken by soaking in deionized water and dried in a vacuum oven at 80°C for 12 hours to further remove water and solvent. The dried membrane is cut into a specified size and stored in a dry state.

[0047] 2. Preparation of eutectic compound: Mix lithium salt lithium bis(trifluoromethylsulfonyl)imide and organic small molecule N-methylacetamide in a mass ratio of 1:1 at 30°C;

[0048] 3. Preparation of dual-phase eutectic polymer solid electrolyte: The dual-phase polymer film and the eutectic compound were adsorbed and combined at a mass ratio of 3:1, and allowed to stand for 4 hours at 80°C for infiltration and adsorption.

[0049] 4. The preparation of soft pack batteries includes the following steps:

[0050] S1: Prepare the battery cell: stack the positive electrode lithium nickel cobalt manganese oxide (811) electrode, the dual-continuous phase eutectic polymer solid electrolyte, and the lithium negative electrode electrode in sequence and fix them, and then package them with aluminum plastic film to obtain the battery cell;

[0051] S2: welding lugs: welding frequency 1000 Hz, time 0.02 s;

[0052] S3: Eutectic compound injection: injection at a mass ratio of 4:1 between the bicontinuous phase polymer film and the eutectic compound;

[0053] S4: Constant temperature standing: The constant temperature standing temperature is 40°C for 4 hours to allow the dual-continuous phase polymer film and the eutectic compound to be fully infiltrated;

[0054] S5: Negative pressure primary pre-packaging: the soaked battery cell is evacuated to negative pressure and packaged, the vacuum degree is -82KPa, and the time is 3s;

[0055] S6: Constant temperature and constant pressure activation: activate the first packaged battery cell in a constant temperature and constant pressure environment, with a constant temperature of 80°C and a constant pressure of 0.8MPa for 6 hours, and test the open circuit voltage and resistance;

[0056] S7: Negative pressure secondary packaging process: the battery is deflated and vacuumed and then packaged again. The vacuum degree is -82KPa and the time is 3s.

[0057] The preparation of soft-pack battery with dual continuous phase eutectic polymer solid electrolyte is completed.

[0058] Example 3

[0059] 1. Preparation of dual-continuous phase polymer membrane: The ion-conducting phase polyether block polyamide and the inert supporting phase polyamic acid are blended in a mass ratio of 4:1, dissolved in a polar solvent N, N-dimethylacetamide to prepare a membrane solution, heated to 80°C in an oil bath, and magnetically stirred for 6 hours. After the polymer is completely dissolved, 15 mL of the dual-continuous phase polymer membrane liquid is quickly dripped on the surface of the glass mold in an area of ​​12×12 cm, and the solvent is evaporated at 80°C to form a membrane. The membrane is taken by soaking in deionized water and dried in a vacuum oven at 80°C for 12 hours to further remove water and solvent. The dried membrane is cut into a specified size and stored in a dry state.

[0060] 2. Preparation of eutectic compound: Mix lithium salt lithium bis(trifluoromethylsulfonyl)imide and organic small molecule N-methylacetamide in a mass ratio of 1:1 at 30°C;

[0061] 3. Preparation of dual-phase eutectic polymer solid electrolyte: The dual-phase polymer film and the eutectic compound were adsorbed and combined in a mass ratio of 3:2, and allowed to stand for immersion adsorption at 80°C for 4 h.

[0062] 4. The preparation of soft pack batteries includes the following steps:

[0063] S1: Prepare the battery cell: stack the positive electrode lithium nickel cobalt manganese oxide (811) electrode, the dual-continuous phase eutectic polymer film, and the lithium negative electrode electrode in sequence and fix them, and then package them with aluminum plastic film to obtain the battery cell;

[0064] S2: welding lugs: welding frequency 1000 Hz, time 0.02 s;

[0065] S3: Eutectic compound injection: injection at a mass ratio of 4:1 between the bicontinuous phase polymer film and the eutectic compound;

[0066] S4: Constant temperature standing: The constant temperature standing temperature is 40°C for 4 hours to allow the dual-continuous phase polymer film and the eutectic compound to be fully infiltrated;

[0067] S5: Negative pressure primary pre-packaging: the soaked battery cell is evacuated to negative pressure and packaged, the vacuum degree is -82KPa, and the time is 3s;

[0068] S6: Constant temperature and constant pressure activation: activate the first packaged battery cell in a constant temperature and constant pressure environment, with a constant temperature of 80°C and a constant pressure of 0.8MPa for 6 hours, and test the open circuit voltage and resistance;

[0069] S7: Negative pressure secondary packaging process: the battery is deflated and vacuumed and then packaged again. The vacuum degree is -82KPa and the time is 3s.

[0070] The preparation of soft-pack battery with dual continuous phase eutectic polymer solid electrolyte is completed.

[0071] Example 4

[0072] The basic process is the same as Example 1, except that: the mass ratio of the ion conductive phase polyether block polyamide and the inert support phase polyamic acid is 1:1, the mass ratio of the lithium salt lithium bistrifluoromethylsulfonyl imide and the organic small molecule N-methylacetamide is 1:5; the mass ratio of the dual continuous phase polymer membrane and the eutectic compound is 1:1.

[0073] Example 5

[0074] The basic process is the same as Example 1, except that: the mass ratio of the ion conductive phase polyether block polyamide and the inert support phase polyamic acid is 10:1, the mass ratio of the lithium salt lithium bistrifluoromethylsulfonyl imide and the organic small molecule N-methylacetamide is 1:10; the mass ratio of the dual continuous phase polymer membrane to the eutectic compound is 10:1.

[0075] The performance parameters of the dual-continuous phase eutectic polymer solid electrolyte and soft-pack battery obtained in each example are shown in Table 1.

[0076] Table 1: Performance parameters of dual-continuous phase eutectic polymer solid electrolyte and soft pack battery

[0077] .

[0078] The above is only a preferred embodiment of the present invention, and does not limit the present invention in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention without departing from the technical solution of the present invention still belongs to the protection scope of the technical solution of the present invention.

Claims

1. A dual-continuous phase eutectic polymer solid electrolyte, characterized in that: The invention is made by infiltrating and adsorbing a eutectic compound on a dual-continuous phase polymer membrane, wherein the dual-continuous phase polymer membrane is made by dissolving an ion-conducting phase and an inert supporting phase in a polar solvent and casting the membrane, wherein the ion-conducting phase is a polyether block polyamide, and the inert supporting phase is one of polybenzimidazole, polyimide, polyamic acid or polyvinyl chloride; the eutectic compound is composed of a lithium salt and an organic small molecule, and the organic small molecule is a Lewis base compound, including one or more combinations of amides, nitriles, carbonates, sulfonic acids and sulfonamide molecules; The ion-conducting phase is the affinity phase of the eutectic compound, while the inert supporting phase is the dispersive phase of the eutectic compound.

2. A dual-continuous phase eutectic polymer solid electrolyte according to claim 1, characterized in that: The mass ratio of the dual-continuous phase polymer to the eutectic compound in the infiltration adsorption is 1-8:

1.

3. A dual-continuous phase eutectic polymer solid electrolyte according to claim 1 or 2, characterized in that: The mass ratio of the ion conducting phase to the inert supporting phase in the dual continuous phase polymer is 1-10:

1.

4. A dual-continuous phase eutectic polymer solid electrolyte according to claim 1 or 2, characterized in that: The eutectic compound is a mixture of lithium salt and organic small molecules in a mass ratio of 1:1-10.

5. A dual-continuous phase eutectic polymer solid electrolyte according to claim 4, characterized in that: The lithium salt is a Lewis acid lithium salt compound, including one or more combinations of lithium bis(trifluoromethylsulfonyl imide), lithium bis(difluorosulfonyl imide), lithium bis(oxalatoborate), lithium perchlorate, lithium tetrafluoroborate and lithium hexafluorophosphate.

6. A method for preparing a soft-pack battery based on the dual-continuous phase eutectic polymer solid electrolyte according to any one of claims 1 to 5, It is characterized in that The method comprises the following steps: S1 preparing the battery cell, S2 welding the tabs, S3 injecting the eutectic compound, S4 standing at a constant temperature, S5 negative pressure primary pre-packaging, S6 constant temperature and constant pressure activation, and S7 negative pressure secondary packaging process; The S1 battery cell preparation method comprises: dissolving the ion conducting phase and the inert supporting phase in a polar solvent and casting the resulting film to obtain a dual-continuous phase polymer membrane; infiltrating and adsorbing the dual-continuous phase polymer membrane in a eutectic compound to obtain a dual-continuous phase eutectic polymer solid electrolyte; and stacking the positive electrode, the negative electrode and the dual-continuous phase polymer membrane and the dual-continuous phase eutectic polymer solid electrolyte in sequence.

7. The method for preparing a soft-pack battery based on a dual-continuous phase eutectic polymer solid electrolyte according to claim 6, characterized in that: The thickness of the dual-continuous phase polymer film is 10 μm~30 μm.

8. A soft pack battery, characterized in that: The dual-continuous phase eutectic polymer solid electrolyte according to any one of claims 1 to 5 is used.

Citation Information

Patent Citations

  • Montmorillonite-based lithium battery solid electrolyte and preparation method thereof

    CN109935894A

  • Solid polymer electrolyte

    CN107851761A

  • Bicontinuous phase gel polymer electrolyte as well as preparation method and application thereof

    CN116505064A

Cited By

  • Polyformaldehyde halide composite solid electrolyte and preparation method thereof

    CN122267271A